PROFESSIONAL PREFERENCES OF SPEECH PATHOLOGIST FOR THE ASSESSMENT AND MANAGEMENT OF DYSPHAGIA AFTER STROKE - Jannat Haider; Rabia Zubair (The Rehabilitation Journal, 2022)
Background: Dysphagia is common after stroke, leading to adverse outcome. The clinical decisions are often based on usual practice, however no formal or similar methods exists to determine the efficacy for assessment and treatment of dysphagia after stroke. Objective:To determine professional preferences among SLPs in terms of opted techniques and approaches for the assessment and management of dysphagia in major cities of Pakistan. Methods:Study design was cross sectional survey and data was collected from practicing speech language pathologists of Rawalpindi, Islamabad, Lahore and Karachi from July 2020 till January 2021through online medium on Google forms. The non-probability convenient sampling technique was used for data collection from speech language pathologists. Sample size was n=31 out of which n=20 were females and n=11 were males. Responses of all participants were presented in the form of n(%) through SPSS version 20. Results: There was variation between all the responses of participants from different cities of Pakistan. The Speech and language pathologists (SLPs)had access to instrumental assessment video fluoroscopy n=5 (16.1%), FEES n= 4 (12.9%) and more than one instrumental assessment tools n= 8 (25.7%) but before recommendation of exercise is rarelyn=20 (64.3%) practiced. The two principal outcome measures for direct dysphagia exercises indicated by SLPs were Oral control n=12 (35.2%) and reduced aspiration n=8 (12.9%). To measure direct exercises outcomes SLPs rarely n=25 (80.7%) uses instrumental assessment tools but use rating scales n=29 (93%). SLPs also prefer to see patient for management of dysphagia 1-2 times a day, 1-4 days a week, for 45 minutes. The most frequently preferred direct exercises are lip range movement n=15 (48.4%), lip strength n=16 (51.6%) and effortful swallow n= 16 (51.6%) whereas electrical stimulation method is least practiced n=5 (16.2%). Conclusion: The Speech language pathologists showed variability in preferences for assessments and management practices and format. Keywords:Dysphagia, clinical decision making, speech-language pathology, stroke.